Extremely high infiltration of CD8+PD-L1+ cells detected in a stage III non-small cell lung cancer patient exhibiting hyperprogression during anti-PD-L1 immunotherapy after chemoradiation: A case report - Wu, Changshun; Zhou, Kai; Zheng, Yan; Lv, Dongxiao; Zhao, Miaoqing; Hu, Yue; Qi, Fei; Wang, Xin; Feng, Hong (Frontiers in Oncology, 2022)
In recent years, Immune checkpoint inhibitors (ICIs), represented by PD-1/PD-L1 monoclonal antibodies, have become a research hotspot in the field of oncology treatment. Immunotherapy has shown significant survival advantages in a variety of solid tumors. However, the phenomenon of Hyperprogressive disease (HPD) in some patients treated with immunotherapy is gradually getting more attention and focus. The early understanding of the characteristics of HPD is crucial to optimize the treatment strategy. We report a patient with unresectable stage III Lung adenocarcinoma who developed HPD with metastasis during consolidation therapy with Durvalumab after chemoradiation. To further investigate the potential mechanism of HPD after anti-PD-L1 treatment, primary lung baseline tissue, baseline plasma, post-immunotherapy plasma and liver metastasis samples of the patient was detected respectively via next-generation sequencing (NGS). Then, multiplex immunohistochemistry (mIHC) was performed on primary lung baseline tissue and liver metastasis samples. KRAS and p.G12C are identified as major driver mutation genes. With a low tumor mutation burden (TMB) value, the patient presented a very high percentage of CD8+ PD-L1+ T cells that infiltrated in the baseline tissue, as 95.5% of all CD8+ cells expressed PD-L1 and low percentage of CD8+ PD-1+ T cells expressed. After the emergence of HPD from immunotherapy, liver metastases were similarly infiltrated with an extremely high proportion of CD8+PD-L1+ T cells, as 85.6% of all CD8+ cells expressed PD-L1, and almost no CD8+PD-1+ T cells expressed. The extreme infiltration of PD-L1+CD8+ T cells in the tumor microenvironment of baseline tissue might be associated with the aggressive tumor growth observed in anti-PD-L1 treatment for related HPD and could be a potential biomarker for HPD development.